Ferulic Acid-Loaded Polymeric Nanoparticles for Potential Ocular Delivery - Alessia Romeo; Teresa Musumeci; Claudia Carbone; Angela Bonaccorso; Simona Corvo; Gabriella Lupo; Carmelina Daniela Anfuso; Giovanni Puglisi; Rosario Pignatello (MDPI AG, 2021)
Ferulic acid (FA) is an antioxidant compound that can prevent ROS-related diseases, but due to its poor solubility, therapeutic efficacy is limited. One strategy to improve the bioavailability is nanomedicine. In the following study, FA delivery through polymeric nanoparticles (NPs) consisting of polylactic acid (NPA) and poly(lactic-co-glycolic acid) (NPB) is proposed. To verify the absence of cytotoxicity of blank carriers, a preliminary in vitro assay was performed on retinal pericytes and endothelial cells. FA-loaded NPs were subjected to purification studies and the physico-hemical properties were analyzed by photon correlation spectroscopy. Encapsulation efficiency and in vitro release studies were assessed through high performance liquid chromatography. To maintain the integrity of the systems, nanoformulations were cryoprotected and freeze-dried. Morphology was evaluated by a scanning electron microscope. Physico-chemical stability of resuspended nanosystems was monitored during 28 days of storage at 5 °C. Thermal analysis and Fourier-transform infrared spectroscopy were performed to characterize drug state in the systems. Results showed homogeneous particle populations, a suitable mean size for ocular delivery, drug loading ranging from 64.86 to 75.16%, and a controlled release profile. The obtained systems could be promising carriers for ocular drug delivery, legitimating further studies on FA-loaded NPs to confirm efficacy and safety in vitro.